Options and Efficiency - Ross, Stephen A. (Quarterly Journal of Economics, 1976)
This paper argues that in an uncertain world options written on existing assets can improve efficiency by permitting an expansion of the contingencies that are covered by the market. The two major results obtained are, first, that complex contracts can be "built up" as portfolios of simple options and, second, that there exists a single portfolio of the assets, the efficient fund, on which all options can be written with no loss of efficiency.